Investigations along the eCommerce user journey: a neuroIS approach with fNIRS to better understand user experience - Nissen, A. (Universität Duisburg-Essen, 2023)
The identification and satisfaction of user needs in business-to-consumer ecommerce is crucial to elicit positive experiences and establish loyalty toward the business. One major interface to the consumer is the website of the business, which can impact the user and customer experience throughout the whole journey. Current approaches that aim to measure user experience (UX) and related constructs have significant shortcomings and are often not able to uncover spontaneous processes in website users. Related neuroIS research proposes that a great part of behavior is formed by these spontaneous processes and that the utilization of additional, neurophysiological measurements can help to uncover these processes and better understand user behavior. Therefore, and to address the shortcomings of common UX measurements in ecommerce, this cumulative thesis presents 6 essays along different UX phases being pre-use, during-use, and post-/repeated-use of the ecommerce website. As a means to assess the spontaneous, potentially unconscious processes, the neuroimaging method fNIRS is utilized in the included essays. Across all papers, several responses to website design factors across UX phases could be identified on the neural level. The complementing self-reported data could reveal these effects only to a certain degree. Consequently, this thesis shows the contribution of neuroimaging (fNIRS) to UX investigation on ecommerce websites to better understand users, which helps to optimize website design and thus, UX.